2011
DOI: 10.1158/0008-5472.can-10-3295
|View full text |Cite
|
Sign up to set email alerts
|

IMP-1 Displays Cross-Talk with K-Ras and Modulates Colon Cancer Cell Survival through the Novel Proapoptotic Protein CYFIP2

Abstract: Insulin-like growth factor 2 mRNA-binding protein-1 (IMP-1) is an oncofetal protein that binds directly to and stabilizes oncogenic c-Myc and regulates, in turn, its posttranscriptional expression and translation. In contrast to normal adult tissue, IMP-1 is reexpressed and/or overexpressed in human cancers. We show that knockdown of c-Myc in human colon cancer cell lines increases the expression of mature let-7 miRNA family members and downregulates several of its mRNA targets: IMP-1, Cdc34, and K-Ras. We fur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
121
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 44 publications
7
121
1
Order By: Relevance
“…Also with roles in nervous system development, CYFIP2 is a p53-inducible gene that leads to caspase activation and apoptosis (35,36). Similarly, CYFIP2 has been shown to negatively modulate survival of colon cancer cells (37). Epigenetic inactivation of SPOCK2 gene is involved in malignant transformation of ovarian endometriosis (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Also with roles in nervous system development, CYFIP2 is a p53-inducible gene that leads to caspase activation and apoptosis (35,36). Similarly, CYFIP2 has been shown to negatively modulate survival of colon cancer cells (37). Epigenetic inactivation of SPOCK2 gene is involved in malignant transformation of ovarian endometriosis (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…We (23,(28)(29)(30)(31). Using quantitative PCR (qPCR), we validated these genes as being hypoxia inducible in a p53-dependent manner in the HCT116 isogenic cell lines (p53 +/+ and p53 -/-) ( Figure 2A).…”
Section: Introductionmentioning
confidence: 98%
“…In addition to GLI1, CRD-BP also has high affinity for several mRNAs whose protein products have been implicated in cancer. These include mRNAs for c-myc (Prokipcak et al, 1994), CD44 (Vikesaa et al, 2006;King et al, 2014), K-Ras (Mongroo et al, 2011), bTrCP1 (Noubissi et al, 2006), microphthalmiaassociated transcription factor (Goswami et al, 2015), mitogenactivated protein kinase 4 (Stohr et al, 2012), b-catenin (Gu et al, 2008), and multi-drug resistance 1 (Sparanese and Lee, 2007). The role of CRD-BP in cancer is further supported by the following findings: 1) Overexpression of CRD-BP in various human cancers, which include colon and breast cancers (Bell et al, 2013), and 2) mice genetically engineered to overproduce CRD-BP in their mammary glands developed mammary adenocarcinoma (Tessier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The role of CRD-BP in cancer is further supported by the following findings: 1) Overexpression of CRD-BP in various human cancers, which include colon and breast cancers (Bell et al, 2013), and 2) mice genetically engineered to overproduce CRD-BP in their mammary glands developed mammary adenocarcinoma (Tessier et al, 2004). Studies on various mRNA targets of CRD-BP have now confirmed that the oncogenic function of CRD-BP results from its physical association with the corresponding mRNAs, leading to their stabilization, increased expression, and ultimately the presentation of the cancerous phenotypes (Noubissi et al, 2006(Noubissi et al, , 2009Vikesaa et al, 2006;Gu et al, 2008;Mongroo et al, 2011). Hence, the ability to disrupt specific CRD-BP-RNA interaction could represent a novel therapeutic approach for the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%